Enantioselective Palladium-Catalyzed CH Functionalization of Indoles Using an Axially Chiral 2,2′-Bipyridine Ligand - Gao, Xiang; Wu, Bo; Huang, Wen-Xue; Chen, Mu-Wang; Zhou, Yong-Gui (Angewandte Chemie International Edition, 2015)
A palladium‐catalyzed enantioselective CH functionalization of indoles was achieved with an axially chiral 2,2′‐bipyridine ligand, thus providing the desired indol‐3‐acetate derivatives with up to 98 % ee. Moreover, the reaction protocol was also effective for asymmetric OH insertion reaction of phenols using α‐aryl‐α‐diazoacetates. This represents the first successful application of bipyridine ligands with axial chirality in palladium‐catalyzed carbene migratory insertion reactions. Get the axial: The title reaction involving diazo compounds was achieved with an axially chiral 2,2′‐bipyridine ligand. Moreover, insertion into OH bonds of phenols was also realized with up to 99 % ee by using this catalytic system.